Combining Medical Informatics and Bioinformatics toward Tools for Personalized Medicine - Sarachan, B. D.; Simmons, M. K.; Subramanian, P.; Temkin, J. M. (Methods of Information in Medicine, 2003)
Objectives: Key bioinformatics and medical informatics research areas need to be identified to advance knowledge and understanding of disease risk factors and molecular disease pathology in the 21st century toward new diagnoses, prognoses, and treatments. Methods: Three high-impact informatics areas are identified: predictive medicine (to identify significant correlations within clinical data using statistical and artificial intelligence methods), along with pathway informatics and cellular simulations (that combine biological knowledge with advanced informatics to elucidate molecular disease pathology).Results: Initial predictive models have been developed for a pilot study in Huntington’s disease. An initial bioinformatics platform has been developed for the reconstruction and analysis of pathways, and work has begun on pathway simulation.Conclusions: A bioinformatics research program has been established at GE Global Research Center as an important technology toward next generation medical diagnostics. We anticipate that 21st century medical research will be a combination of informatics tools with traditional biology wet lab research, and that this will translate to increased use of informatics techniques in the clinic.
Keywords: Bioinformatics; medical informatics; pathway informatics; predictive medicine; cellular simulations